A Comparative Study of Bisoprolol with Carvedilol on LV Systolic Function in Patients with Chronic Heart Failure - Hossain, Mohammad Ashraf; Ahmed, Khurshed; Kabir, Md Faisal Ibn; Khaled, Md Fakhrul Islam; Rashed, Rakibul H; Amin, Md Al; Khondoker, Md Noornabi; Md Jamil, Abu Baqar; Islam, Md Mesbahul; Bajracharya, Prashant; Hoque, Harisul (University Heart Journal, 2018)
Background: Chronic heart failure (CHF) is the most common and prognostically unfavorable outcome of many diseases of the cardiovascular system. Recent data suggest that beta-blockers are beneficial in patients with CHF. Among β-blocker class of drugs, bisoprolol is a highly selective β1-adrenergic receptor blocker whereas Carvedilol is non-selective. Many large-scale trials have confirmed that both these β-blockers are superior to placebo and other β-blockers. This study was designed to compare the effects of carvedilol and bisoprolol in patients with chronic HF in a single center. Methods: It was a quasi experimental study. A total of 288 cases of heart failure were selected by purposive sampling, from January 2017 to June 2017. Each patient was allocated into either of the two groups, and was continued receiving treatment with either bisoprolol (Group-I) or carvedilol (Group-II). Each patient was evaluated clinically and echocardiographically at the beginning of treatment (baseline) and at the end of 3rd month. Echocardiography was performed to find out change in left ventricular systolic function. Result: After 3 months of treatment, ejection fraction was found higher in the bisoprolol group (42.6 ± 6.5 versus 38.3 ± 4.6%; P < 0.05). Ejection fraction (EF) changes were 8.4% in bisoprolol group and 4.1% in carvedilol group. A significant reduction in left ventricular end-systolic volume (21.9±2.5 in group I versus 14.9±5.7 in group II; P < 0.05) and left ventricular systolic diameter (3.2±0.1 in group I versus 2.3±0.5 in group II; P<0.05) occurred after 3 months of treatment. But no significant differences were observed in left ventricular end-diastolic volume (10.1±3.2 versus 6.1±6.4; P=0.101) and left ventricular diastolic diameter (1.7±0.8 versus 1.3±0.8; P=0.081) between groups. Three months after treatment, heart rate was reduced in the bisoprolol group from 87.7±9 to 74.5±8.1 and carvedilol group from 88.8±9.1 to 80.1±8.7. Differences in heart rate responses between 2 groups were not statistically significant (P=0.113). Assessment of blood pressure three months later of treatment shows, systolic blood pressure (SBP) and diastolic blood pressure (DBP) were improved in both group but difference between two groups were statistically non significant (p>0.05). Conclusion: In this study, bisoprolol was superior to carvedilol in increasing left-ventricular ejection fraction, improving left ventricular end systolic volume and left ventricular end systolic diameter but no significant difference was observed in LV end diastolic volume, LV end diastolic diameter, heart rate and blood pressure. University Heart Journal Vol. 14, No. 1, Jan 2018; 3-8